The effect of social entitlement programs on private transfers: New evidence of crowding out - Kristopher Gerardi; Yuping Tsai (Federal Reserve Bank of Atlanta, 2010)
This paper exploits a natural policy experiment to directly identify the crowding out effects of public transfers on the incidence and level of private transfers. The introduction of a large social security program in Taiwan is used to estimate the effect of an exogenous increase in government transfer payments to the elderly on the private transfer behavior of their adult children. Using an instrumental variables strategy that accounts for the endogeneity of receiving public transfers, the empirical results show strong evidence of crowding out on the extensive margin (the probability of providing a positive transfer) and weaker evidence of crowding out on the intensive margin (the amount of the transfer conditional on it being positive.
Keywords: H53; H55; H31; 330; private transfers; crowding out